2019
DOI: 10.21203/rs.2.16979/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of spiritual care training to enhance spiritual health and spiritual care competency among oncology nurses

Abstract: Background: Although spiritual care is a basic element of holistic nursing, nurses' spiritual care knowledge and abilities are often unable to satisfy patients' spiritual care needs. Therefore, nurses are in urgent need of relevant training to enhance their abilities to provide patients with spiritual care. Design: A non-randomized controlled trial. Objective : To establish a spiritual care training protocol and verify its effectiveness. Methods: This study recruited 92 nurses at a cancer-treatment hospital … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The findings indicated that the training program increased self-perceived competency of the intervention group in integrating clients’ R/S in clinical practice significantly and with a very large effect size. Similar to the present study, several studies reported positive effects of the training programs on spiritual care competencies and integration of clients’ R/S into clinical practice in healthcare providers, including nurses and nursing students [ 22 , 23 , 31 33 ]. Pearce et al (2019) conducted an interventional online study that increased spiritual competencies and integration of clients’ R/S into practice among mental healthcare providers.…”
Section: Discussionsupporting
confidence: 87%
“…The findings indicated that the training program increased self-perceived competency of the intervention group in integrating clients’ R/S in clinical practice significantly and with a very large effect size. Similar to the present study, several studies reported positive effects of the training programs on spiritual care competencies and integration of clients’ R/S into clinical practice in healthcare providers, including nurses and nursing students [ 22 , 23 , 31 33 ]. Pearce et al (2019) conducted an interventional online study that increased spiritual competencies and integration of clients’ R/S into practice among mental healthcare providers.…”
Section: Discussionsupporting
confidence: 87%
“…What is seen in studies that include evaluations by patients, is that they benefit from a change in practice after staff have attended courses. Hu et al (2019, S3) claim that nurses with spiritual health have a better ability to recognise and respond to patients’ spiritual needs and are more likely to proactively provide spiritual care to patients. Other studies indicate that training in spiritual care for healthcare professionals may have positive effects on the quality of care as reported by patients (van de Geer et al, 2017, S14; Vlasblom et al, 2011, S35).…”
Section: Discussionmentioning
confidence: 99%
“…Students who had attended spiritual care courses could acquire more spiritual care knowledge and had a deeper understanding of spiritual care, making them more willing to apply spiritual care into their practice. Studies also suggested that additional nursing spiritual education could improve spiritual care awareness, knowledge, and skills (Green et al, 2020; Hu et al, 2019; Rachel et al, 2019). Similarly, studies found that not including spiritual care courses in nursing programs is a barrier to providing spiritual care (Musa et al, 2019; Ross et al, 2018).…”
Section: Disussionmentioning
confidence: 99%